Artists Revolution - Artists Revolution (Philippines Artists Revolution, 2010)
A Filipino film production created by Artists Revolution, featuring original script, cast, and direction, highlighting contemporary social themes. Satirical Skits on Voters' Education
Filipino independent production.
General audience
Keywords: Filipino; Voters Education